Pengaruh Covid-19 Terhadap Perekonomian Setiap Negara Menggunakan Python - Oktavia, Kinanti; Taufiq, M; Wijaya, Riko Setya (Jurnal Ilmiah Wahana Pendidikan, 2023)
The Covid-19 outbreak caused many restrictions that impacted the global economy. Almost all countries have been negatively affected by the increase in Covid-19 cases. This study aims to find out how Covid-19 affects the global economy. This Covid-19 impact analysis uses Python. The research subjects in this study are the top 10 countries with the highest number of Covid-19 cases. This research uses quantitative research with a quantitative descriptive approach. This research utilizes the use of several existing libraries in the Python programming language in analyzing the impact of Covid-19 as a data source based on the growth of GDP per capita for each country. The results of this study indicate that the per capita GDP of each country has relatively decreased during the Covid-19 outbreak.